Temperamento de búfalas em lactação e suas relações com o uso do espaço e a produção e qualidade do leite - Carvalhal, Monique Valéria de Lima [UNESP] (2014)
The production of dairy buffaloes in Brazil is going through a moment of increased investments on the production mechanization systems, which is promoting, mostly, the intensification of milk production. Given this intensification, it is important to broaden the understanding of the behaviour of dairy buffaloes in order to base recommendations for the good practices of handling. One of the most relevant behavioral aspects for the understanding of individual differences is the concept of temperament. Temperament is a complex phenomenon that involves several intrinsic characteristics of the individual. The aim of this study was to evaluate the relationship between two behavioral indicators of temperament and the implications of these characteristics on milk yield and milk quality. The first chapter was developed with the purpose of contextualizing the reader about the mainly subjects of the dissertation. The second chapter, regarding the observational study, was designed to evaluate the association between the reactivity levels of dairy buffaloes during milking and the distances traveled daily by these animals; besides we focus to evaluate the effects of these temperament indicators on the production and the quality of milk. We conclude that there is individual variation in the reactivity of buffaloes in the milking parlour, and also for the consistency of this characteristic. For animals with a high degree of consistency, the intense reactivity during milking has deleterious effects on the production and quality of milk. We also concluded that the distance traveled daily by the buffaloes is not associated with their reactivity during milking; and have no effect on the animals’ productivity. Finally, the implications of this research have been described in chapter three